Classical (Generalized) Utilitarianism and the Repugnant Conclusion - Shiell, Leslie (Université d'Ottawa | University of Ottawa, 2004)
Both classical and critical-level generalized utilitarianism (CGU and CLGU) exhibit the repugnant conclusion on an unrestricted choice set when repugnance is defined in terms of the critical level. However, contrary to common belief, the repugnant conclusion is not an inherent feature of utilitarian population principles. Rather, it results from the interaction of the principles with certain choice sets. Choice sets can be assessed in terms of their realism, defined as conformity with universal properties of physics, biology and preferences. It is shown that these properties entail a particular structure of choice set on which CGU and CLGU do not exhibit the repugnant conclusion.
Keywords: variable-population social choice; utilitarianism; repugnant conclusion